1979
DOI: 10.1111/j.1600-0765.1979.tb00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive properties of periodontal dressings‐an in vitro study

Abstract: The adhesive properties of three periodontal dressing materials to hard and soft tissues were studied in vitro. The results indicated that adhesion occurred between the tissues and two of the materials. The third material did not adhere to any of the surfaces tested. Only small adhesive forces were recorded, but they may be of importance in establishing a tight seal between the dressings and the tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…The lower value obtained by the latter authors may be explained by the higher cross-head speed (1 0 mm/minute) employed in their investigation. Haugen et al ( 1979) measured the tensile bond strength of a zinc oxide-eugenol based periodontal pack to dentine as 0.2MN/m2. This is higher than those for the zinc oxide-eugenol based products, Endom&hasone and N2 Normal, but clearly lower than for ProcoSol as recorded in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The lower value obtained by the latter authors may be explained by the higher cross-head speed (1 0 mm/minute) employed in their investigation. Haugen et al ( 1979) measured the tensile bond strength of a zinc oxide-eugenol based periodontal pack to dentine as 0.2MN/m2. This is higher than those for the zinc oxide-eugenol based products, Endom&hasone and N2 Normal, but clearly lower than for ProcoSol as recorded in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Peripac requires no mixing, but its elastic properties and solvent loss both present problems. They may well account for the known problem of adaptation in the mouth (Gjerdet & Haugen, 1977), and are also likely to be responsible for the poor level of adhesion to enamel shown by this material (Watts & Combe, 1980;Haugen et al, 1979).…”
Section: Critique Of Materialsmentioning
confidence: 99%
“…Recent work in this field concerns such matters as dimensional change on setting (Gjerdet & Haugen, 1977) and adhesion (Watts & Combe, 1980;Haugen, Espevik & Mjor, 1979).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent study showed that, of three current dressings, Coe-Pak® had the best retention to enamel (approximately 0.3MN/m^ tetisile bond, and 0.5MN/m^ shear bond), and these were suggested as lower limits in the quest for a more retentive material (Watts & Combe 1980). A study with a different methodology (Haugen et al 1979) gave a similar result with regard to tensile bonding, and suggested that the presence of salivary pellicle might enhance the adhesive properties of Coe-Pak. In their 1980 study the present authors suggested a possible level of adhesion for future development of adhesive dressings, but at the time, no data were available on the maximum permissible level of retention, given the clinical need for removal of dressings after a short period of time.…”
mentioning
confidence: 99%